Subsidence and Percentage of CO2 Emission from Decomposition to Subsidence of Peatland on Oil Palm Plantations - Affan Chahyahusna; Dwi Putro Tejo Baskoro; Syaiful Anwar (AGRIVITA, Journal of Agricultural Science, 2022)
Peatlands drainage system aimed to eliminate the limiting factors to support better growth of plants. Drainage practices will cause subsidence and be associated with CO2 emission. The purpose of this study was to observe the subsidence rate on tropical peatlands of oil palm plantations at different ages and to establish the percentage of decomposition of peat materials from the subsidence rate. Subsidence was measured in 9-, 12-, and 17-year-old of adjacent oil palm planting blocks with peat thickness of about 5 m and have been drained for 10–18 years, two samples taken for each block every three month. Peat decomposition was measured in the 12-year-old block automatically using LiCor Li-8100A with 30 minutes recording interval. Peat decomposition (heterotrophic respiration) considered as actual CO2 emission was compared to emission calculated from subsidence and considered as potential CO2 emission. The average subsidence rate observed for one year in the three age classes of oil palm plantations was 2.47 ± 0.76 cm/year. The percentage of CO2 emissions from the decomposition process to subsidence on drained 12-year-old oil palm on tropical peatlands was 41.05%. The subsidence data indicates that consolidation still the main process of subsidence in this peatland.